Combining technology and work organization: An analysis of complementarity between IT and decentralization across firms of different size - Fabienne Rasel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper examines whether information technology (IT) and decentralized work organization are complementary only for large firms or also for smaller firms. Empirical evidence, which suggests complementarity between IT and decentralization, is mainly based on large firms. Using data from a sample of 3292 SMEs and of 598 larger firms from the manufacturing and service sector in Germany, I can observe firms' IT intensity in terms of enterprise software and computer use and whether firms have a decentralized work organization. I find that SMEs with decentralized work practices tend to use IT more intensively. Moreover, for the sample of SMEs, IT and decentralized work organization are individually associated with higher productivity but the combination of IT and decentralization does not yield a productivity premium. Contrarily, for the sample of larger firms, the results show that the productivity of IT depends positively on decentralization. The findings suggest that combining IT and decentralized work organization seems to be a successful strategy only for larger firms.
urn:nbn:de:bsz:180-madoc-371507
Keywords: D22; D24; L20; O33; 330; information technology; decentralized work organization; complementarity; productivity; enterprise software; firm-level data